A human adventure – an address to the Interval Symposium 2013. Issue 1 (2014) - Claude Henri Chevrier
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to explore the operationalizing of a philosophy of humanization of hostel care and the challenge to such development presented by the proposed adoption of the "housing first" approach ("Chez Soi D'Abord") in Paris. Design/methodology/approach – The paper is a translation of the transcript of an address given by the author to a symposium of psycho‐analytic therapists working with the homelessness resettlement services in their quarter of Paris. It is a narrative of service development, described in some practical detail, with philosophical and psycho‐analytic depths. Findings – A philosophy of care and social education is replacing the philosophy of surveillance that had characterized earlier development of hostels. Psycho‐analytic concepts, based on the writings of Lacan, help to understand the importance of addressing the profound psycho‐social dislocation of individuals subject to the implicit violence of their situation. Originality/value – This is the first known paper in print and in English to describe the development of a psychologically informed environment in homelessness resettlement in France. <ack> <x xml:space="preserve"> Acknowledgements </x> This paper is a transcript of a speech given at L'Intervalle, a symposium of psychotherapists, Paris, 28 September 2013. It was translated by: Claude Chevrier, John Conolly, Helene Fletcher and Robin Johnson. </ack>